2013
DOI: 10.18632/aging.100539
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a small molecule activator of SIRT1 gene expression

Abstract: Increased SIRT1 expression exerts beneficial effects in transgenic animal models, ameliorating the onset and progression of aging-related disease phenotypes in various organs including the heart. The potential beneficial effects of SIRT1 have made SIRT1 a prime therapeutic target for age-related diseases and considerable efforts led to the identification of small molecule activator of SIRT1 protein. Thus far, however, a small molecule activator of SIRT1 gene expression has not been reported. Here, we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In the future, we will test whether administration of antibiotics could abolish the effect of SYR on immune and endocrine system in the SPF mice. In addition, given the fact that SIRT1 and FOXO3 participate in the regulation of glucose metabolism and Treg homeostasis467475, and SYR induces the activation of SIRT1 and FOXO331 (Fig. 3), still there is a possibility that SYR may have a direct effect on the level of blood glucose as well as Treg homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, we will test whether administration of antibiotics could abolish the effect of SYR on immune and endocrine system in the SPF mice. In addition, given the fact that SIRT1 and FOXO3 participate in the regulation of glucose metabolism and Treg homeostasis467475, and SYR induces the activation of SIRT1 and FOXO331 (Fig. 3), still there is a possibility that SYR may have a direct effect on the level of blood glucose as well as Treg homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, there have been no reports regarding SYR metabolism by gut microbiota and the effects of SYR on modulation of the gut microbiota. Recently, we demonstrated that SYR delays cellular senescence and alleviates hypoxia/reoxygenation injury through the activation of FOXO33031. SYR stimulated the nuclear translocation of FOXO3, leading to the transcriptional activation of its target genes involved in the antioxidant and anti-inflammatory effects30.…”
mentioning
confidence: 99%
“…For example, increase of dSir2 transcription is observed in the long-lived mutant flies and calorierestricted normal flies [60]. It was found, that pharmacological agents resveratrol [61], polydatin [62], syringaresinol [63], and phloridzin [64], which are known to have anti-aging effect and relive senescence-associated patologies, induces expression of the SIRT1 homologues too.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ginsenoside-free molecules promote ethanol metabolism [127]. Recently, a lignin compound, syringaresinol(4,4'-(1S,3aR,4S,6aR)-tetrahydro-1H,3H-furo[3,4-c]furan-a,4-diylbis(2,6-dimethoxyphenol)), was isolated from panax ginseng pulp and found to activate SIRT1 gene expression, leading to delayed cellular senescence and improved endothelial cell function in endothelial cells [128]. Syringaresinol treatment induced the binding of FOXO3 to the SIRT1 promoter in a sequence-specific manner, leading to the induction of SIRT1 expression.…”
Section: Exploring Other Bioactive Constituents In the Ginseng Berry mentioning
confidence: 99%